ON WEAK ?-STATISTICAL CONVERGENCE OF ORDER ? - Ercan, Sinan; Altin, Yavuz; Bektas, Cigdem A. (Univ Politehnica Bucharest, Sci Bull, 2018)
In the present paper, we give the concept of weak lambda-statistical convergence of order alpha and weakly [V, lambda]-summability of order alpha. Some relations between of these concepts and also some relations between weak lambda-statistical convergence of order alpha and strong lambda-statistical convergence of order alpha are examined.
Keywords: Weak statistical convergence; Cesaro Summability